The midfacial glomangiopericytoma - Case report - Bogna Zielińska-Kaźmierska; Joanna Grodecka; Dominika Teodorczyk-Werfel; Radosław Milcarz (Elsevier, 2015)
Glomangiopericytoma is classified as a borderline low malignancy tumor but recurrence rate is reported to be about 16.8%-30%, probably caused by the lack of radical resection.1 It is a rare tumor arising from pericytes surrounding capillaries. The tumor has a predilection for the nasal cavity and paranasal sinuses.We report a case of glomangiopericytoma with an aim to present how it can invade and destroy both maxillary bones and lower part of nasal cavity. Due to its dimensions the tumor required extensive resection within tumor-free margins. On the basis of immunohistochemical staining the tumor was diagnosed as glomangiopericytoma.Strict follow-up of 16 months after radical resection revealed no recurrence of the tumor.